2022
DOI: 10.1042/etls20220002
|View full text |Cite
|
Sign up to set email alerts
|

The bed nucleus of the stria terminalis in threat detection: task choice and rodent experience

Abstract: Behavioural reactivity to potential threat is used to experimentally refine models of anxiety symptoms in rodents. We present a short review of the literature tying the most commonly used tasks to model anxiety symptoms to functional recruitment of bed nucleus of the stria terminalis circuits (BNST). Using a review of studies that investigated the role of the BNST in anxiety-like behaviour in rodents, we flag the certain challenges for the field. These stem from inconsistent methods of reporting the neuroanato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…Although fMRI resolution has greatly improved in recent years [e.g., ( 2 )] it is unclear whether most, or indeed any, of the studies reported in Table 1 of Daniel-Watanabe and Fletcher ( 1 ) have enough resolution to differentiate the CeA: in humans, this structure is very small, representing only a minute percentage of amygdala volume, estimated at about 3% ( 2 ). Similarly, the BNST is a small and exceedingly complex structure ( 3 ), only representing a small portion of the area measured as BNST in some fMRI studies, e.g., see Figure 3 in Grupe et al. ( 4 ).…”
mentioning
confidence: 99%
“…Although fMRI resolution has greatly improved in recent years [e.g., ( 2 )] it is unclear whether most, or indeed any, of the studies reported in Table 1 of Daniel-Watanabe and Fletcher ( 1 ) have enough resolution to differentiate the CeA: in humans, this structure is very small, representing only a minute percentage of amygdala volume, estimated at about 3% ( 2 ). Similarly, the BNST is a small and exceedingly complex structure ( 3 ), only representing a small portion of the area measured as BNST in some fMRI studies, e.g., see Figure 3 in Grupe et al. ( 4 ).…”
mentioning
confidence: 99%